Dengue haemorrhagic fever: An emerging disease in Nigeria, West Africa - Ademola H. Fagbami; Anyebe B. Onoja (Elsevier, 2018)
Introduction: In Nigeria, dengue fever caused by dengue virus, types 1 and 2 has been diagnosed for many years. Although, seroepidemiological surveys have shown that dengue virus activity is, widespread in the country, there is scanty information on dengue, hemorrhagic fever with little attention paid to dengue fever largely, because it presents as classical dengue fever characterized by fever, myalgia, headache, arthralgia, retro-orbital pain, gastro intestinal, symptoms and skin rash. We are updating the current information of dengue, in Nigeria, as well as DHF which is an emerging disease in the west, African country. Methods: PUBMED, Google scholar, cross-reference databases and individual publications not publicly archived were used. All available literature on, dengue from Nigeria were identified. Results: Dengue virus 3 and 4 have been recently detected in Nigeria, with the emergence of dengue haemorrhagic fever for the first time. Poor, surveillance, underreporting, and misdiagnosis of the disease as malaria, are major problems. Conclusion: Priority must be given to increasing surveillance activity to, detect more dengue haemorrhagic fever cases and determine the magnitude, of the dengue problem. It is important to enhance the capacity of, laboratories to diagnose dengue haemorrhagic fever by providing them with, modern equipment, reagents and new infrastructure. Keywords: Dengue haemorrhagic fever, Emerging disease, Nigeria